Understanding the concept and importance of the health research system in Palestine: a qualitative study - Mohammed AlKhaldi; Yehia Abed; Constanze Pfeiffer; Saleem Haj-Yahia; Abdulsalam Alkaiyat; Marcel Tanner (BMC, 2018)
Abstract Background The importance of a health research system (HRS), namely an instrument for developing and enabling health systems, is increasing, particularly in developing countries. Assessing the perceptions of system performers is a necessary part of system analysis, which seeks to recognize a system's strengths and limitations aiming towards improvement. This study assesses the perceptions of policy-makers, academicians and experts regarding the HRS concept and its importance to generate insights for system strengthening. In Palestine, HRS is just emerging, helping to address the many public health-related challenges faced by the country. Methods The study was implemented from January until July 2016, targeting three sectors, namely relevant government institutions, schools of public health, and major local and international health agencies. Data was collected through 52 in-depth interviews and six focus group discussions (FGDs) with policy-makers, academics, directors and experts. Participants and institutions were selected based on stated criteria and peer review. Data were translated, transcribed, checked and then imported to a software program (MAXQDA 12) for thematic and content analysis. Results A total of 104 experts participated, wherein 52 were interviewed and 52 participated in the six FGDs. The HRS concept, as defined by WHO, was conceptualized differently among participants with unclear delineations between various components. Inconsistencies appeared when participants attempted to conceptualize HRS in broader contexts, though HRS goals and functions were sufficiently delineated. The majority of participants agreed that HRS correlates with notions of 'improvement' and recognized HRS 'as a significant gain'. Neglect of HRS was perceived as a big loss. Conclusions The study revealed that the level of understanding of HRS among health experts in Palestine is inadequate and not sufficiently conceptualized for its application. Findings also underlined the need to establish a central governance coordination body that promotes HRS understanding, awareness and culture as an enabler for HRS strengthening.